Development of a Low Cost Programmable Logic Controller - Kay, Marcel Seiji; Iaione, Fábio; Barbosa, Andréa Teresa Riccio; Sacchi, Rodrigo Porfírio da Silva; Odakura, Valguima Victoria Viana Aguiar (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Some Brazilian regions have an agricultural vocation and are undergoing on a significant industrialization process, which is mainly caused by the installation of biofuel industries. Therefore, demand for agricultural and industrial automation will be great in the next years. The aim of this study is to develop a low cost small module (hardware card), for use in the automation of simple machines and equipments. This programmable logic controller (PLC) will be part of an open platform that also contains a free software tool for programming PLC in C language, and an online tutorial with detailed instructions about building and programming the system. Thus, students and professionals can automate machinery and equipment in a simple and low cost way. This article shows the electronic design of the PLC, its programming and tests results of the breadboard setup.